CORM-2 inhibits intracerebral hemorrhage-mediated inflammation. (3rd October 2021) - Chen, Zhiying; Zhang, Huiyan; Zhou, Jun; Stone, Christopher; Ding, Yuchuan; Zhang, Yunzhou; Ren, Changhong; Yin, Xiaoping; Meng, Ran
ABSTRACT: Background and purpose : Low-dose of carbon monoxide delivered by CO-releasing molecule-2 (CORM-2) had been confirmed having anti-inflammatory efficacy in some inflammatory diseases. Herein, we assessed the usefulness of CORM-2 in correcting intracerebral hemorrhage (ICH)-mediated inflammation. Methods : Healthy male Sprague Dawley (SD) rats randomly entered into four groups: sham-ICH, ICH, ICH+CORM-2, and ICH+ inactive carbon monoxide releasing molecule 2 (iCORM-2). ICH was induced by 50 μl of autologous arterial blood injected in situ in the rat brain. Neuro-functions of the ICH rats were evaluated with Garcia 18 scores at the 6th, 24th, 48th hou, and the fifthh day post-ICH. And brain tissues surrounding the hematoma area were collected from all ICH rats and assayed with Western blot and immunofluoresence analysis. Results : Neuro-dysfunctions in ICH rats were very severe than those in ICH +CORM-2 rats. Compared to sham group, the levels of HO-1, IKKβ, NF-κB, and TNF-α in ICH group began to elevate at the 6th hour, and reached to peak at the 48th hour post-ICH, all p < 0.05. While in ICH +CORM-2 group, the expressions of IKKβ, NF-κB, and TNF-α were very weaker than that in ICH group at every time points mentioned above; however, this phenomenon was not reproduced in ICH + iCORM-2 group. HO-1 in ICH+CORM-2 group highlighted in perihematomal area with many activated microglia (Iba-1-positive cells) and co-expressed with TNF-α, all of which were diminished at the fifth day post-ICH. Conclusion : CORM-2 may attenuate ICH-mediated inflammation by inhibiting microglial activation, which may involve the IKK/NF-κB pathway. Abbreviations ICH: intracerebral hemorrhage; CO: carbon monoxide; CORM-2: carbon monoxide releasing molecule-2; iCORM-2: inactive carbon monoxide releasing molecule-2; HO-1: heme oxygenase 1; IKKβ: inhibitor of IκB kinases β; NF-κB: nuclear factor-κB; TNF-α: tumor necrosis factor-α; Iba-1: ionized calcium binding adaptor molecule-1; IκB: inhibitor of NF-κB; iNOS: inducible nitric oxide synthase; Keap1: Kelch-like ECH-associated protein 1; Nrf2: NF-E2-related factor 2; DMSO: dimethylsulfoxide